Some Functional Properties of Blondo-Calcium Mix - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
Blondo is a solid residue of the wet coconut milk oil extraction process. The oil extraction from coconut milk, which is facilitated by adding CaySO4, produced blondo-calcium mix residue. This reildue was studied for its stability as a high protein food ingredient. Blondo-calcium mix contains 77.6% protein with water retention capacity of 2 ml water/g (less than skim milk powder but greater than casein) and oil retention similar to those of skim milk powder or casein. The emulsion capacity of blondocalcium mix was slightly lower (70%) than that of skim milk powder or casein at pH 6 and 8 but slightly higher at pH 2 and 10. The emulsion stability of blondo-calcium was lowest at pH 4 and 6, but highest at pH 2. Blondo-calcium mix is probably best to be used in a low pH food emulsion system (such as in non-dairy yogurt).